The IFS Green Budget: October 2023 - Carl Emmerson; Paul Johnson; Ben Zaranko (Institute for Fiscal Studies (IFS), 2023)
The Chancellor is in a fiscal bind as low growth and high debt interest payments limit any room for manoeuvre in the forthcoming Autumn Statement.
Keywords: 330; Government finances and spending; Taxes and benefits; IFS Green Budget 2023; Fiscal performance; Government spending; Tax